Zhu Rongji on the Record : The Road to Reform 1991-1997 - Zhu, Rongji, 1928- (Book collections on Project MUSE., 2013)
China's explosive transformation from a planned economy to a more market-oriented one over the past three decades owes much to the charismatic reformer Zhu Rongji. His pragmatism and strong work ethic have been key forces in China's drive to greater modernization and global stature. He served as the mayor and party chief in Shanghai from 1987 to 1991, as vice premier of China from 1991 to 1998, and then as premier until 2003. This monumental collection brings together, for the first time in English, over one hundred important speeches, articles, letters, and instructions written during his term as vice premier, when he had major responsibility for fulfilling Deng Xiaoping's vision and setting China on a new and fruitful course.